Television violence and young adults in Brazil: a content analysis of the popular telenovella, Malhação = Violência na televisão brasileira e jovens : uma análise de conteúdo da telenovela popular, Malahção - Campbell, Debra Frances [UNESP] (2015)
The problem of this study was to examine the prevalence, or salience, of general television violence and sex-related violence on a widely popular Brazilian television program for teenagers, Malhação (Workout, in English), and to determine what types of violence are depicted. The purpose of this investigation, therefore, was first: to identify if and how violent content occurs in a Brazilian television program designed for young viewers, the telenovella, Malhação (Part 1); and secondly, to quantify sex-related violence, particularly forms that involve misogyny, gender stereotypes, and messages and images that reinforce the sexualization of teens (Part 2). The study employed two specific quantitative content analysis protocols to measure frequency and duration of violent content that reflect general and sexrelated violence. We determined types, categories and subcategories, and intensity of violence. Also, we included an analysis of demographic variables (i.e., age, race, and gender) in the program's storylines. For the first part of the study, our results confirmed the existence of a large proportion of scenes with violent content, although this appeared at a level of subtle and, therefore, low intensity. Two types were identified, priming for violence (PRI) and overt violence (VIO). Within our sample, the VIO type dominated the scenes. The highest incidence occurred in the category/subcategory of intrapersonal/psychological violence. Males were more involved in overt violence, and females in psychological violence. Teens appeared predominantly as perpetrators, and less as victims, than did adults. In the second part of the study, our results confirmed a trend towards representations of misogyny, stereotypes, female objectification, and the sexualization of female teens, as well as the acceptance of inappropriate behaviors by institutions (school and family) and the community in ...